A+2(y+3)=y+7

Simple and best practice solution for A+2(y+3)=y+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for A+2(y+3)=y+7 equation:


Simplifying
A + 2(y + 3) = y + 7

Reorder the terms:
A + 2(3 + y) = y + 7
A + (3 * 2 + y * 2) = y + 7
A + (6 + 2y) = y + 7

Reorder the terms:
6 + A + 2y = y + 7

Reorder the terms:
6 + A + 2y = 7 + y

Solving
6 + A + 2y = 7 + y

Solving for variable 'A'.

Move all terms containing A to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + A + -6 + 2y = 7 + -6 + y

Reorder the terms:
6 + -6 + A + 2y = 7 + -6 + y

Combine like terms: 6 + -6 = 0
0 + A + 2y = 7 + -6 + y
A + 2y = 7 + -6 + y

Combine like terms: 7 + -6 = 1
A + 2y = 1 + y

Add '-2y' to each side of the equation.
A + 2y + -2y = 1 + y + -2y

Combine like terms: 2y + -2y = 0
A + 0 = 1 + y + -2y
A = 1 + y + -2y

Combine like terms: y + -2y = -1y
A = 1 + -1y

Simplifying
A = 1 + -1y

See similar equations:

| 6f-4+2f=20 | | 6x-8+15=-9 | | -6x-3x=5(x-5)-3(7x+1) | | 3(-0.8+0.4y)+2y=0 | | (7r-4)(r+5)-(2r-1)(r+5)= | | 2(3y+7)=44 | | (3x+1)+(8x-24)= | | 0=.333x+4 | | -y^2=0 | | 14u-9u=45 | | 13=y+20 | | 3(-5+5x)-2x=11 | | t^2-2t=(t+3) | | 5+4w=-3 | | -3(w+4)=3w-30 | | 8+3x=19+x | | U-184=39 | | D/-2=36 | | 10(x-2)+8=12 | | 2x+2(x-5)=38 | | 4(x-8)-6x=-12 | | z^7+5z^6=0 | | 5m+m=12 | | 7/x=2-3/x | | 1078/14 | | 3r^2=2+7r | | 22=d-2 | | 4y+8=4 | | -4(5n+4)=-16-n | | -9w-4=14 | | x^2+3x-1=7x+22 | | -3(2p+4)=-15-5p |

Equations solver categories